P685 Healthcare resource use associated with ferric maltol and IV iron treatment for iron deficiency anaemia in patients with inflammatory bowel disease. (15th January 2020) - Howaldt, S; Jacob, I; Sampson, M; Akriche, F
Abstract: Background: Iron deficiency anaemia (IDA) is common in patients with inflammatory bowel disease (IBD). IDA imposes a substantial economic burden on healthcare payers resulting primarily from increased medical costs and increased rates of hospital admission. Most guidelines recommend oral iron as first-line treatment, with IV iron if oral supplementation is ineffective or poorly tolerated. Intolerance to ferrous (Fe2+) oral iron is common in patients with IBD. Ferric maltol (FM), a stable oral complex of ferric (Fe3+) iron and maltol, is designed to reduce exposure to elemental iron and thus limit gastrointestinal damage. This analysis compares the Healthcare resource use (HCRU) associated with oral FM and IV ferric carboxymaltose (FCM) treatment. Methods: Patients with IBD and IDA (haemoglobin [Hb] ≥8.0 g/dl and ≤11.0 g/dl for women or ≥8.0 g/dl and ≤12.0 g/dl for men, and ferritin <30 ng/ml or ferritin <100 ng/ml with transferrin saturation <20%) were randomised to FM (30 mg b.i.d) or IV FCM (as per local SmPC) in an open-label, Phase 3b non-inferiority study. The primary endpoint was Hb responder rate (proportion of patients achieving a ≥2 g/dl increase or normalisation of Hb at week 12); the margin for non-inferiority was 20%. HCRU was assessed based on the total costs of iron therapy (including drug costs and administration), and the number of hospital/outpatient visits during the initial 12-week study period. Costs of IV FCM and FM were applied to a German setting. Results: 250 patients were randomised: 125 to FM and 125 to IV FCM. The primary endpoint was not met. Mean (standard deviation; SD) total treatment costs per patient in the FM and IV FCM arms were €302.27 (€80.68) and €489.37 (€147.19) respectively. Eighty-seven per cent of FM patients were still receiving treatment at week 12, and 45% and 36% of IV FCM patients required a repeat course of IV iron at weeks 4 and 12, respectively. The mean (SD) number of hospital/outpatient visits during the study period for patients receiving IV FCM was 2.30 (0.88) and the total dose of IV FCM received was 1621 mg (491 mg). Conclusion: Total per patient drug costs were approximately 1.6 times higher for treatment with IV FCM than FM. The total cost of IV FCM is not only influenced by the higher drug cost, but additional costs associated with IV administration which was required to be carried out in a hospital or outpatient setting. FM has no additional costs or resource use associated with administration and is, therefore, less of a burden on local healthcare systems. FM is associated with substantially lower HCRU than IV FCM, and may provide a cost-effective oral alternative to IV iron in patients with IBD.